Assessing the Efficacy and Efficiency of Subsidiary Silvicultural Operations in Sal Forest of Jharkhand; Measuring the Impact in terms of Ecosystem Services - Gupta, H. S.; Prasad, S.; Prasad, S. (Indian Forester, 2023)
This study is aimed at evaluation of ecological and economical value of Subsidiary Silvicultural Operations (SSOs) in Sal forest of Jharkhand, by measuring its effects in terms of Ecosystem Services (ES) . Data like plant height and girth etc. were collected, from 18 samples and 18 control plots , spread over 3 Agroclimatic Zone, for three models of SSOs . Using the collected data, parameters like wood volume, Biomass, Shannon Wiener Index (Hâ€™) , Regeneration status and Soil conserved / ha. were generated .Comparative analysis between sample and control plot shows, SSOs where practised has led to alter significantly, the productivity and biodiversity of forest . In sample plot wood volume growth assessed was 107 m3 /ha. ; Biomass growth 54 m3 /ha , Carbon content 27m3 /ha. Regeneration percentage as calculated 44.45%. Shannon Wiener Index (Hâ€™) was found 1.39 and the average of the same for control plots was found to be ; wood volume 61.53 m3 /ha. ; Biomass 20.11 m3 /ha. , carbon content 10.05 m3 /ha. ; Regeneration percentage 28.51% and Shannon Wiener Index (Hâ€™) 1.09/ha. Thus in general, SSOs have a positive effect on all the parameters of ecosystem services. Soil conservation effect is found highest in â€œNorthern dry mixed forestâ€ i.e. 21.1 m3 /ha. Subsequently 16.57 m3 /ha in mixed moist and dry deciduous forest and lowest 13.55 m3 /ha. in dry peninsular Sal forest. All the factors like wood volume, biomass, and carbon content, Shannon Wiener Index, regeneration status, soil conservation are important measures for sustainability of any given ecosystem. Therefore SSOs need to be 1promoted to ensure, conserve and increase forest productivity ultimately, achieving sustainable Forest Management, like soil conservation, natural regeneration and biological diversity etc. Study also evaluated the various ES of Forest in terms of monetary value and has found that per hectare enhancement of Rs. 225838 happened in ES NDMF, RS. 324746 in MMDDF and RS. 385120 in DPSF measured by difference between sample and control plot. This gives very significant hope when the same is analysed at Ì’ Ì’ Forest type level. for this efficacious intervention i.e. SSOs The result showed that in Model no.3 of SSO is the best and dry peninsular Sal forest of Jharkhand as compared with Model no.1, 2 and forest sub type similarly for NDMF, MMDDF.